The Essence of Giving Food as The Spirit of Islam in The Book "الاءطعام روح الاءسلام " by Syeh Ali Bin Ali Bin Ibrahim U'dhobi - Khumaimah, Rinatul; Anisah, Zulfatun (Proceedings of International Conference on Muslim Society and Thought, 2024)
Social disparities are prevalent in our society. The imbalance in life and the terrifying contradictions among human lives continue to this day. These imbalances occur globally. We witness countries devastated by war, such as Palestine, Yemen, and Syria, where the inhabitants suffer from hunger and lack access to healthcare. Similarly, countries with high poverty rates like Cambodia, Myanmar, and Afghanistan experience hunger and poor sanitation. Conversely, there are many developed and prosperous countries with high income levels in other parts of the world. This study employs a literature review approach, examining verses from the Qur'an and hadiths of the Prophet Muhammad SAW concerning Ith’am as contained in the book "الاءطعام روح الاءسلام" by Syekh Ali bin Ali bin Ibrahim U’Dhobi. The book explains that Islam encourages people to help each other, have empathy, sympathy, and high social concern. As mentioned in Surah Adh-Dhariyat, verse 19: "And in their wealth, there is a right for those who ask and those who do not ask." Therefore, it is essential for Muslims to pay significant attention and care to convey and study the core teachings of Islam contained in Ith’am (charity by giving food). The five pillars of Islam (shahadah, prayer, fasting, zakat, and hajj) are the foundation of Islam and must be performed to be recognized as a Muslim. The pillars of Islam are closely related to Ith’am, making it a core teaching of Islam (the spirit of Islam).